English and Nature: An Ecocritical Study Through English Narrative Text - Widyaiswara, Tiara; Luthfiyati, Dian; Nurman, Moh.; Nadhiah, Sirli (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
The urgency of this research is due to the problems being faced by Indonesia regarding the destruction of nature and the lack of human awareness of the relationship between humans and nature, which is an important factor behind the destruction of nature that is happening today. The author uses eco-ELT theory as an approach that integrates environmental issues into English language learning. The subject of this study is narrative text in the English textbook "English for Nusantara" for junior high school grade 9. This study requires the creation and implementation of an English textbook that employs the Eco-ELT approach and qualitative methods. According to the findings of this study, natural disasters, shelter, animals, and the earth can all be used to depict the environment. The English textbook "English for Nusantara" contains materials relevant to the Eco-ELT program, which is aligned with five types of interventions: material, experiential, cognitive, and emotional, all of which conceptualize the relationship between humans and nature.